Corporate parent value addition and challenges - Abdullah, Haim Hilman; Mehmood, Khawaja Khalid (IDOSI Publications, 2013)
Corporate parent value addition is essential and challenging aspect of corporate strategy.Corporate managers can add value to their company's business portfolio by developing a good understanding of the businesses and using corporate level capabilities to improve businesses' strategic position.Effective management of corporate center results in several ways for adding value to the businesses.Alternatively, undue treatment of business portfolio could lead to value destruction. Despite its supreme importance, this area didn't receive enough treatment by empirical research in past. Future research can unfold new perspectives in corporate parenting and add significant contribution to field of corporate strategy.